Rezolvati ecuatia:12-2×(3x-1)=-4,unde x€Z
Răspunsuri la întrebare
Răspuns de
4
12-2×(3x-1)=-4,unde x€Z;
12-6x+2=-4;
14-6x=-4;
14+4=6x;
18=6x;
x=18:6;
x=3
x€Z din ambele =>S={3}
12-6x+2=-4;
14-6x=-4;
14+4=6x;
18=6x;
x=18:6;
x=3
x€Z din ambele =>S={3}
Răspuns de
5
12-2×(3x-1)= -4
12-6x+2= -4
14-6x= -4
-6x= -4-14
-6x= -18 |×(-1)
6x=18
x=18:6
x=3€ Z
12-6x+2= -4
14-6x= -4
-6x= -4-14
-6x= -18 |×(-1)
6x=18
x=18:6
x=3€ Z
Alte întrebări interesante
Limba română,
8 ani în urmă
Geografie,
8 ani în urmă
Engleza,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Informatică,
9 ani în urmă
Matematică,
9 ani în urmă